Perancangan Jaringan Nirkabel Berbasis Mesh untuk Menunjang Aplikasi Smart City - Fauzan Prasetyo Eka Putra; Mustafida Mustafida; Royhan Alfadili; Afifatun Nahriyah (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The development of the Smart City concept demands a reliable, flexible communication network infrastructure capable of covering the entire urban area. This study designs a wireless network based on mesh topology as a communication solution to support various Smart City applications. Mesh topology is chosen for its advantages in scalability, path redundancy, and fault tolerance. The research method involves designing a network simulation with varying numbers of nodes and testing performance parameters such as throughput, latency, and packet loss. Simulation results show that an increase in the number of nodes correlates with higher throughput, lower latency, and reduced packet loss. These findings indicate that mesh topology is highly suitable for meeting the real-time and stable connectivity needs of Smart City implementations. This network design is expected to serve as a foundation for future digital infrastructure development in smart cities.